2017
DOI: 10.1063/1.4990566
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the bias-driven migration of oxygen vacancies in amorphous non-stoichiometric gallium oxide

Abstract: The conductivity of gallium oxide thin films is strongly dependent on the growth temperature when they deposited by pulsed laser deposition under vacuum environment, exhibiting an insulative-to-metallic transition with the decrease of the temperature. The high conductive gallium oxide films deposited at low temperature are amorphous, non-stoichiometric, and rich in oxygen vacancy. Large changes in electrical resistance are observed in these non-stoichiometric thin films. The wide variety of hysteretic shapes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…[ 35 ] Wu et al fabricated a series of gallium oxide thin films on sapphire substrate via PLD with T s ranging from 250 to 650 °C and found that the crystallization procedure started at about 450 °C as well as a blue shift presenting at the absorption edge (from 4.6 to 5.1 eV) with T s increasing from 450 to 650 °C. [ 37 ] In the study by Guo et al, [ 74 ] gallium oxide films were deposited on α‐Al 2 O 3 substrates at various T s (500, 550, 600, 650, and 700 °C) in a vacuum environment. At low growth temperature (500 °C), the film is XRD amorphous, strong oxygen deficiency, low transparency, and high conductivity.…”
Section: Preparation Methods Of A‐gaoxmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 35 ] Wu et al fabricated a series of gallium oxide thin films on sapphire substrate via PLD with T s ranging from 250 to 650 °C and found that the crystallization procedure started at about 450 °C as well as a blue shift presenting at the absorption edge (from 4.6 to 5.1 eV) with T s increasing from 450 to 650 °C. [ 37 ] In the study by Guo et al, [ 74 ] gallium oxide films were deposited on α‐Al 2 O 3 substrates at various T s (500, 550, 600, 650, and 700 °C) in a vacuum environment. At low growth temperature (500 °C), the film is XRD amorphous, strong oxygen deficiency, low transparency, and high conductivity.…”
Section: Preparation Methods Of A‐gaoxmentioning
confidence: 99%
“…I – V hysteretic loop and current‐turning voltage of the amorphous sample is strongly dependent on the voltage‐sweep rate, which can be attributed to the migration of V O defects driven by bias. [ 74 ] Heinemann et al investigated oxygen deficiency and Sn doping in a‐GaO x thin films grown at a temperature gradient from 425 to 300 °C and from 160 to 100 °C with fixed oxygen partial pressure of 2 × 10 −5 and 1.3 × 10 −3 mbar, respectively. [ 75 ] All the films show an amorphous structure for T s up to 425 °C.…”
Section: Preparation Methods Of A‐gaoxmentioning
confidence: 99%
“…Several experimental investigations have shown that gallium oxide and especially amorphous, substoichiometric gallium oxide thin films (a-GaO , ) exhibit resistive switching 4 11 . In contrast to other known resistive switching oxides, such as titania 12 , 13 or strontium titanate 14 , 15 , a-GaO does not need a forming process 4 , 6 , 8 , 9 . According to both experimental and simulation results, the resistive switching can be based on a change in bulk resistance due to the migration of oxygen ions between the blocking electrodes of the device 4 , 6 , 8 , 9 .…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to other known resistive switching oxides, such as titania 12 , 13 or strontium titanate 14 , 15 , a-GaO does not need a forming process 4 , 6 , 8 , 9 . According to both experimental and simulation results, the resistive switching can be based on a change in bulk resistance due to the migration of oxygen ions between the blocking electrodes of the device 4 , 6 , 8 , 9 . Therefore, the resistance scales with the size of the memristive device, which is an advantage for the downsizing of devices in later applications.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation